2012
DOI: 10.3171/2012.7.peds11455
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological profiles and outcomes in pediatric patients with intracranial aneurysms

Abstract: Object Intracranial aneurysms are extremely uncommon in the pediatric population, their characteristics are not well studied, and certain features make them unique. The authors analyzed pediatric patients with aneurysms to try to understand their clinical, radiological, and outcome profile. Methods Sixty-three pediatric patients (≤ 18 years of age) with ages ranging from 4 to 18 years and features (clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
1
40
1
Order By: Relevance
“…Dissecting aneurysms in particular can lead to mass effect, hemorrhage, or ischemia [6]. There are few reports of incidentally found UIA in children during routine autopsy studies [6,8]. Given that a majority of pediatric UIAs are symptomatic, treatment is important in order to prevent aneurysm rupture or worsening of symptoms due to UIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissecting aneurysms in particular can lead to mass effect, hemorrhage, or ischemia [6]. There are few reports of incidentally found UIA in children during routine autopsy studies [6,8]. Given that a majority of pediatric UIAs are symptomatic, treatment is important in order to prevent aneurysm rupture or worsening of symptoms due to UIA.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of intracranial aneurysms is estimated to range from 0.5 to 4.6 % among those 18 years of age or younger [1,3,8,[10][11][12]. Aneurysms in the pediatric population differ significantly from those in the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Saraf et al 19 reported that endovascular management is a safe, durable, and effective treatment for pediatric intracranial aneurysms. Considering the substantial rise in the use of flow diverters among all contemporary endovascular devices in adults, it is expected that these devices will be used with increasing frequency in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the better clinical grades at presentation is unclear but may be attributable to several factors, such as few comorbidities and a greater tendency among physicians to refer cerebrovascular cases to tertiary care centers. 31 Second, good long-term outcomes may be partially attributable to the low prevalence of symptomatic CV due to the robustness of the cerebral collateral circulation in children. However, the 3 children who experienced symptomatic CV also had relatively good long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%